2014
DOI: 10.1002/micr.22230
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 61 unplanned readmission cases in microvascular free tissue transfer patients: Multi‐institutional analysis of 774 patients

Abstract: In our study, the presence of either open wound/wound infection, development of surgical complications, medical complications, and unplanned reoperations were associated with unplanned readmissions. Further research in predictive factors is suggested to avoid costly, unnecessary, and preventable readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Both Carniol et al and Kim et al found SSIs to be predictive of 30-day readmission in patients undergoing free flap reconstruction. 5,9 Moreover, wound complications as a major determinant of readmission has been a consistent finding across the surgical literature. Graboyes et al found that a SSI or wound dehiscence was associated with a nearly sevenfold increase in the risk of readmission in a large population of otolaryngology patients.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Both Carniol et al and Kim et al found SSIs to be predictive of 30-day readmission in patients undergoing free flap reconstruction. 5,9 Moreover, wound complications as a major determinant of readmission has been a consistent finding across the surgical literature. Graboyes et al found that a SSI or wound dehiscence was associated with a nearly sevenfold increase in the risk of readmission in a large population of otolaryngology patients.…”
Section: Discussionmentioning
confidence: 78%
“…These results are in keeping with the literature. Both Carniol et al and Kim et al found SSIs to be predictive of 30‐day readmission in patients undergoing free flap reconstruction . Moreover, wound complications as a major determinant of readmission has been a consistent finding across the surgical literature.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…8,19 Unplanned 30-day readmission rates following free tissue transfer can range from 7.9% to 11.6%. 19,20 Therefore, our finding of higher 30-day readmission rates following laryngeal and oropharyngeal cancer surgery may be related to both greater procedure complexity and patient complexity when compared to patients undergoing other otolaryngology procedures.…”
Section: Discussionmentioning
confidence: 90%